Hybridity, conflict, and the global politics of cybersecurity - Moving forward: fragmentation, polarization, and hybridity (2023)
Cyberspace has become the ultimate frontier and central issue of international conflict, geopolitical competition, and security. Emerging threats and technologies continuously challenge the prospect of an open, secure, and free cyberspace. Additionally, the rising influence of technology on society and culture increasingly pushes international diplomacy to establish responsible state behavior in cyberspace and internet governance against the backdrop of fragmentation and polarization. In this context, novel normative practices and actors are emerging both inside and outside the conventional sites of international diplomacy and global governance. In this open access title, Fabio Cristiano and Bibi van den Berg explore the hybridity and conflict inherent to these recent processes of remodulation of the global politics of cybersecurity by analyzing emerging normative practices, threats and technologies, and actors. Through this comprehensive analysis, this edited volume ultimately sheds light on the problematic technical logic of emergence that informs the global politics of cybersecurity and delineates novel normative paths for cyberspace moving forward. The ebook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com. Open access was funded by Leiden University